Strengthening behavior of carbon/metal nanocomposites - Shin, S. E.; Choi, H. J.; Hwang, J. Y.; Bae, D. H. (NATURE PUBLISHING GROUP, 2015)
Nanocomposites reinforced with nano-scale reinforcements exhibit excellent mechanical properties with low volume fraction of the reinforcement. For instance, only an addition of 0.7 vol.% few-layer graphene (FLG) into the pure titanium shows strength of similar to 1.5 GPa, obviously much superior to that of the monolithic titanium. The strengthening efficiency of composites is determined by several factors such as reinforcement geometrical/spatial characteristics and interfacial features between the matrix and the reinforcement. For the metal-matrix nanocomposites (MMNCs), since the nanoscale reinforcement has significantly high specific surface area, interfacial feature is more important and has to be clearly evaluated in understanding property of MMNCs. Although many researchers suggested the theoretical work using continuum mechanics in order to estimate the mechanical properties of the metallic composites, a clear determination has yet not to be proven by systematic experimental works. Here, we provide a new model to predict strength and stiffness of MMNCs based on quantitative analysis of efficiency parameters in which interface feature is strongly emphasized. To validate the model, we select multi-walled carbon nanotube (MWCNT) and FLG for reinforcement, and titanium (Ti) and aluminum (Al) for the matrix to modify bonding strength and specific surface area in the MMNCs.
Keywords: MATRIX; COMPOSITES